2021
DOI: 10.1097/brs.0000000000004272
|View full text |Cite
|
Sign up to set email alerts
|

Formal Patient Complaints and Malpractice Events Involving Orthopedic Spine Surgeons

Abstract: Study Design. Case-control study. Objective. To analyze patient complaints, potential risk, and malpractice events involving orthopedic spine surgeons over a 10-year period. Summary of Background Data. Unsolicited patient complaints may be associated with risk management and malpractice events. Methods. We analyzed patient complaint, potential risk event, and malpractice event data for six orthopedic spine surgeons over a 10-year period. Patient complaints were analyzed and classified according to the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[12] Other reasons for spinal malpractice suits Other reasons were identified for patients filing spinal malpractice actions. [Table 1] [6,16] 1]. [6] Analyzing 214 complaints from 202 patients for spine-related malpractice events (i.e.…”
Section: Lack Of Informed Consentmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Other reasons for spinal malpractice suits Other reasons were identified for patients filing spinal malpractice actions. [Table 1] [6,16] 1]. [6] Analyzing 214 complaints from 202 patients for spine-related malpractice events (i.e.…”
Section: Lack Of Informed Consentmentioning
confidence: 99%
“…[6] Analyzing 214 complaints from 202 patients for spine-related malpractice events (i.e. involving 6 orthopedic spine surgeons over a 10 year period), Rae et al (2022) further identified a 35% incidence of the "lack of access to the surgeons postoperatively", and another 32% cited failures in postoperative care/treatment (i.e. including 34 dissatisfied with postoperative results) [Table 1].…”
Section: Lack Of Informed Consentmentioning
confidence: 99%
See 1 more Smart Citation